Cost-effectiveness of CT perfusion for patients with acute ischemic stroke (CLEOPATRA)-Study protocol for a healthcare evaluation study. (June 2022) - Koopman, Miou S; Hoving, Jan W; van Voorst, Henk; Daems, Jasper D; Peerlings, Daan; Buskens, Erik; Lingsma, Hester F; Marquering, Henk A; de Jong, Hugo WAM; Berkhemer, Olvert A; van Zwam, Wim H; van Walderveen, Marianne AA; et al.
Introduction: Computed tomography perfusion (CTP) is variably considered to assess eligibility for endovascular thrombectomy (EVT) in acute ischemic (AIS) stroke patients. Although CTP is recommended for patient selection in later (6–24 h) time window, it is currently not recommended in the earlier (0–6 h) time window and the costs and health effects of including CTP for EVT selection remain unknown. We aim to estimate the costs and health effects of using CTP for EVT selection in AIS patients compared to conventional selection. Patients and methods: CLEOPATRA is a healthcare evaluation study using clinical and imaging data from multiple, prospective EVT trials and registries in both the earlier and later time windows. To study the long-term health and cost effects, we will construct a ("Markov") health state transition model simulating the clinical outcome over a 5-year follow-up period for CTP-based and conventional selection for EVT. Clinical data acquired within the current study and estimates from the literature will be used as input for probabilities of events, costs, and Quality-Adjusted Life Years (QALYs) per modified Rankin Scale (mRS) subscore. Primary outcome for the cost-effectiveness analysis will be the Incremental Cost-Effectiveness Ratio (ICER) in terms of costs per QALY gained over the simulated follow-up period. Study outcomes: Outcome measures will be reported as cumulative values over a 5-year follow-up period. Discussion: This study will provide preliminary insight into costs and health effects of including CTP in the selection for EVT for AIS patients, presenting between 0 and 24 h after time last known well. The results may be used to develop recommendations and inform further implementation projects and studies.